Peculiarities of the early recovery period in patients with cerebral ischemic stroke, depending on the presence of type 2 diabetes - Runcheva, K. A. (Запорізький державний медичний університет, 2022)
Aim of the research:To analyze the features of the early recovery period in patients with cerebral ischemic stroke (CIS) depending on the presence of T2D.
Keywords: тези доповідей